Aripiprazole IV - Hudson, B. (My University, 2022)
Inelastic Neutron Scattering spectrum of Aripiprazole IV, C23H27Cl2N3O2, measured on the TOSCA instrument. 7-{4-[4-(2,3-Dichlorophenyl)piperazin-1-yl]butoxy}-3,4-dihydroquinolin-2(1H)-one
Keywords: TOSCA